Influence of the COVID-19 quarantine on biodiversity and conservation research during 2020 - the Peruvian case - Tori, Martha (2022)
The lockdown was the measure taken by the Peruvian state as a response to the pandemic caused by COVID-19. This imposition meant a delay for almost all sectors, including the academic sector. This study analyzes the repercussions of the lockdown through scientific work in Peru in 2020, focusing on subjects of biodiversity and conservation. We conducted a during July and August of 2020, which was answered by 111 researchers. Results of the survey show that the most affected research area was field research due to the restrictions; and that the most affected group were women, which presented the highest percentages of dissatisfaction, both in their work and emotional state. This research reveals the reality of a country with a historically low investment in research, and now the work of many researchers is restricted due to the current economic and employment situation due to the pandemic. Its replication in other Latin American countries could be of help for future policies in favor of academic research.